Enhancing Business Agility in the USA Retailers Through Integration of Enterprise Agility and Intelligence - Kumar, Rishi (Digital Repository of Theses, 2024)
This dissertation explores the integration of agility and intelligence within the U.S. retail sector, examining how these strategic dimensions enhance operational effectiveness and competitive advantage. The study utilizes a robust quantitative analysis, drawing responses from a survey of 201 retail professionals across the United States, to assess the adoption levels, impacts, and challenges associated with these strategies. Agility and intelligence are recognized as critical levers for retail businesses to adapt swiftly to market changes and consumer demands. The research findings indicate that a significant majority of retailers have embraced agile practices and intelligence integration, with about 65% of businesses reporting high levels of agile adoption and similarly robust integration of artificial intelligence (AI) and business intelligence (BI) tools. These strategies are closely interconnected, as firms excelling in agility also tend to leverage advanced data analytics and AI more effectively. Despite the clear benefits, integrating agility and intelligence is not without challenges. The study identifies resistance to change, technical difficulties, and cost barriers as the primary hurdles. However, these challenges also present substantial opportunities for growth and improvement. For instance, overcoming resistance through comprehensive change management strategies can lead to deeper and more effective adoption of new technologies. The effectiveness of strategic roadmaps in guiding the integration process was found to be variable, with about 50% of businesses feeling that their strategic roadmaps could be more well-defined. This suggests a need for clearer and more actionable planning to fully harness the potential of agility and intelligence. Furthermore, the integration of these strategies significantly enhances business competitiveness, with retailers reporting improvements in customer satisfaction, market responsiveness, and operational flexibility. The dissertation underscores the essential role of agility and intelligence in modern retail operations. The findings advocate for a strategic, well-rounded approach to adopting these practices, which can lead to substantial improvements in operational efficiency and strategic decision-making. Retail leaderships are advised to invest not only in technologies but also in cultural and procedural transformations that support ongoing adaptability and improvement, ensuring sustainable growth and competitiveness in the evolving retail landscape.